Discordant Effects of Cannabinoid 2 Receptor Antagonism/Inverse Agonism During Adolescence on Pavlovian and Instrumental Reward Learning in Adult Male Rats - Ellner, Danna; Hallam, Bryana; Frie, Jude A.; Thorpe, Hayley H. A.; Shoaib, Muhammad; Kayir, Hakan; Jenkins, Bryan W.; Khokhar, Jibran Y. (Frontiers in Synaptic Neuroscience, 2021)
The endocannabinoid system is responsible for regulating a spectrum of physiological activities and plays a critical role in the developing brain. During adolescence, the endocannabinoid system is particularly sensitive to external insults that may change the brain’s developmental trajectory. Cannabinoid receptor type 2 (CB2R) was initially thought to predominantly function in the peripheral nervous system, but more recent studies have implicated its role in the mesolimbic pathway, a network largely attributed to reward circuitry and reward motivated behaviour, which undergoes extensive changes during adolescence. It is therefore important to understand how CB2R modulation during adolescence can impact reward-related behaviours in adulthood. In this study, adolescent male rats (postnatal days 28-41) were exposed to a low or high dose of the CB2R antagonist/inverse agonist SR144528 and Pavlovian autoshaping and instrumental conditional behavioral outcomes were measured in adulthood. SR144528-treated rats had significantly slower acquisition of the autoshaping task, seen by less lever pressing behaviour over time (F2, 19 = 5.964, p = 0.010). Conversely, there was no effect of adolescent SR144528 exposure on instrumental conditioning. These results suggest that modulation of the CB2R in adolescence differentially impacts reward-learning behaviours in adulthood.